2017
DOI: 10.1073/pnas.1704663114
|View full text |Cite|
|
Sign up to set email alerts
|

A study of problems encountered in Granger causality analysis from a neuroscience perspective

Abstract: , we misunderstood the method described in Barnett and Seth (25) to compute the conditional Granger causality. We realize now that the spectral factorization method they describe can be used to obtain the conditional Granger causality with a single model fit, which would avoid the computational problems associated with separate model fits. We apologize for this error." Granger causality methods were developed to analyze the flow of information between time series. These methods have become more widely applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
206
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(206 citation statements)
references
References 56 publications
0
206
0
Order By: Relevance
“…In particular, whereas cortical inhibitory networks can generate β oscillations (26) that slow to α frequencies with increasing inhibitory tone (13), propofol-induced α oscillations appear to become coherent through the functional influence of the thalamus (14). We must emphasize, however, that the presence of thalamocortical coherence implies only an interaction between the two areas, and cannot convey directional influences, which would require the application of different analysis methods that can be challenging to interpret (27). During emergence, these propofol-induced dynamics dissipated, but with a trajectory that differed from that observed during induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, whereas cortical inhibitory networks can generate β oscillations (26) that slow to α frequencies with increasing inhibitory tone (13), propofol-induced α oscillations appear to become coherent through the functional influence of the thalamus (14). We must emphasize, however, that the presence of thalamocortical coherence implies only an interaction between the two areas, and cannot convey directional influences, which would require the application of different analysis methods that can be challenging to interpret (27). During emergence, these propofol-induced dynamics dissipated, but with a trajectory that differed from that observed during induction.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14).…”
mentioning
confidence: 99%
“…Specifically, A ! In recent years, criticism about pairwise GC analysis has been growing (Smith, 2012;Barnett et al, 2017), leading to the development of newer approaches for information flow estimation such as the one implemented in the present investigation (Stokes & Purdon, 2017;Faes, Stramaglia, & Marinazzo, 2017;Seth et al, 2013). The method applied here stem from Granger Causality (GC) analysis, and it is based on the concepts of predictability and precedence: variable A is said to modulate variable B if the past behavior of A contains information that helps predict the future behavior of B over and above information already in the past of B.…”
Section: Directed Information Flow Analysismentioning
confidence: 99%
“…In a time window of 800–900 ms, we found significant causality from alpha power to the ERFs (Granger coefficient = 0.161, corrected p = .0064), while causality from the ERFs to alpha power was nonsignificant (Granger coefficient = 0.05, uncorrected p = .09). Those results suggested that a dissociation of ERFs between F‐A and F‐NA trials (beginning from 890 ms) resulted from temporal dynamics of alpha rhythm in the same time window (800–900 ms), although results of the Granger causality analysis should be interpreted cautiously (Stokes & Purdon, ).…”
Section: Resultsmentioning
confidence: 99%